2016
DOI: 10.1111/1540-6229.12170
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation between Local Amenities and House Price Dynamics

Abstract: This study explores the extent to which local amenities are related to house price volatility, returns and risk‐adjusted returns across 238 MSAs. We find strong evidence that high amenity areas experience greater price volatility. In regards to returns, high amenity areas experience greater (lower) real returns in appreciating (depreciating) markets. However, high amenity areas experience little to no abnormal risk‐adjusted returns. Results from the study are robust to an endogenous treatment of amenities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Meanwhile, an increase in amenities in small-medium cities leads to an increase in the second cost of population urbanization, which is correlated with urban amenities, such as housing costs. As Beracha et al (2018) show, housing costs are higher in high urban amenities areas. Overall, the costs from an increase in amenities in small-medium cities are higher than the benefits from this increase and harm population urbanization as a result.…”
Section: Results From Panel Model Regressionmentioning
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, an increase in amenities in small-medium cities leads to an increase in the second cost of population urbanization, which is correlated with urban amenities, such as housing costs. As Beracha et al (2018) show, housing costs are higher in high urban amenities areas. Overall, the costs from an increase in amenities in small-medium cities are higher than the benefits from this increase and harm population urbanization as a result.…”
Section: Results From Panel Model Regressionmentioning
confidence: 93%
“…Some studies have shown that land prices in areas adjacent to parks, transportation stations, shopping centers, primary and secondary schools, and high-quality medical facilities tend to be high (Huh and Kwak, 1997;Jim and Chen, 2007). Urban amenities and housing values have been found to be highly positively correlated (Beracha et al, 2018). Thus, to maximize profits from the changes in residential land, local governments are well motivated to improve urban amenities.…”
Section: Theoretical Analysis and Hypotheses Developmentmentioning
confidence: 99%
“…Other recent research that examined externalities/amenities and the effect on property include Diao, Qin and Sing () who examined rail noise impact on house values; Beracha and Hardin () who examined school quality on renter and owner housing; Rouwendal, Levkovich and van Marwijk () who examined the impact that proximity to water has on house values and Beracha et al . () who examined local amenities and house price dynamics.…”
mentioning
confidence: 99%
“…in areas where price developments are unstable. Volatility is higher in urban areas with good access to local amenities (Beracha et al, 2016), i.e. in attractive urban areas.…”
Section: Underlying Mechanismsmentioning
confidence: 97%